Vagon 03 . Vagon 03 . Car 03 . Вагон 03 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program devoted to discussing the economic and social problems in Ingushetia and which includes an interview with the republic's President. Featured in the program: Aushev, Ruslan Sultanovich (President of Ingushetia) Программа посвящена экономическим и социальным проблемам Ингушетии и включает интервью с Президентом Ингушетии. В программе участвуют: Аушев, Руслан Султанович (Президент Ингушетии)